The company-university relationship as a strategic tool in organizational learning management. - Salomon, Maria Fernanda Barbato; Silva, Carlos Eduardo Sanches da (Revista Gestão da Produção Operações e Sistemas, 2007)
This article highlights aspects from the Company-University relationship, considering its impact and importancefor an organization learning management. A bibliographical research was used to mention the main conceptsof learning organization. It is concluded that the Company-University relationship, still incipient in Brazil, consistsof a complex process, which consolidates itself through financial results, in which the government attempsto support this cooperation. For the companies to values the learning process, they must promote changes thatencourage information and knowledge exchange for both involved parts.Keywords: Companies; Universities, Learning Organization.